The Role of Thermal Denudation in Erosion of Ice-Rich Permafrost Coasts in an Enclosed Bay (Gulf of Kruzenstern, Western Yamal, Russia) - Baranskaya, Alisa; Novikova, Anna; Shabanova, Natalya; Belova, Nataliya; Maznev, Stepan; Ogorodov, Stanislav; Jones, Benjamin M. (Frontiers in Earth Science, 2021)
Coastal erosion in the Arctic has numerous internal and external environmental drivers. Internal drivers include sediment composition, permafrost properties and exposure which contribute to its spatial variability, while changing hydrometeorological conditions act as external drivers and determine the temporal evolution of shoreline retreat. To reveal the relative role of these factors, we investigated patterns of coastal dynamics in an enclosed bay in the southwestern Kara Sea, Russia, namely the Gulf of Kruzenstern, which is protected from open-sea waves by the Sharapovy Koshki Islands. Using multitemporal satellite imagery, we calculated decadal-scale retreat rates for erosional segments of the coastal plain from 1964 to 2019. In the field, we studied and described Quaternary sediments and massive ground-ice beds outcropping in the coastal bluffs. Using data from regional hydrometeorological stations and climate reanalysis (ERA), we estimated changes in the air thawing index, sea ice-free period duration, wind-wave energy and total hydrometeorological stress for the Gulf of Kruzenstern, and compared it to Kharasavey and Marre-Sale open-sea segments north and south of the gulf to understand how the hydrometeorological forcing changes in an enclosed bay. The calculated average shoreline retreat rates along the Gulf in 1964-2010 were 0.5±0.2 m yr-1; the highest erosion of up to 1.7±0.2 m yr-1 was typical for segments containing outcrops of massive ground-ice beds and facing to the northwest. These retreat rates, driven by intensive thermal denudation, are comparable to long-term rates measured along open-sea sites known from literature. As a result of recent air temperature and sea ice-free period increases, average erosion rates rose to 0.9±0.7 m yr-1 in 2010-2019, with extremes of up to 2.4±0.7 m yr-1. The increased mean decadal-scale erosion rates were also associated with higher spatial variability in erosion patterns. Analysis of the air thawing index, wave energy potential and their total effect showed that inside the Gulf of Kruzenstern, 85% of coastal erosion is attributable to thermal denudation associated with the air thawing index. Our findings highlight the importance of permafrost degradation and thermal denudation on increases in ice-rich permafrost bluff erosion in the Arctic.